Implementasi Gerakan Sekolah Sehat di Sekolah Dasar Negeri 26 Mataram - Khosiah, Khosiah; Hasanah, Uswatun; Rahmawati, Fitri Indah; Nurhamida, Nurhamida; Hardiyanti, Eka; Nurrahmi, Nurrahmi; Sholihah, Mar'atun; Putri, Lilis Regina; Ayun, Fanya Kurata; Maulana, A'an (Universitas Muhammadiyah Mataram, 2025)
Abstract: The School Health Movement is a strategic step to improve the quality of health and education in Indonesia. The purpose of this movement is to improve the physical and mental health conditions of students, as well as to create a clean, safe, comfortable school environment that supports children's growth and development. The implementation of this activity uses observation, interviews, and documentation methods to obtain data and information related to the implementation of the school health movement at SDN 26 Mataram. The implementation of the School Health Movement has shown positive results in various aspects of physical health, mental health, and cleanliness of the school environment. Although there are still some challenges in its implementation, active participation from all school components, parents, and the community is very important in ensuring the success of this movement. The Healthy School Movement can continue to grow and provide long-term benefits for students, schools, and the community as a whole.Abstrak: Gerakan Sekolah Sehat merupakan salah satu langkah strategis untuk meningkatkan kualitas kesehatan dan pendidikan di Indonesia. Tujuan kegiatan Gerakan ini diluncurkan untuk memperbaiki kondisi kesehatan fisik dan mental peserta didik, serta menciptakan lingkungan sekolah yang bersih, aman, nyaman, dan mendukung tumbuh kembang anak. Pelaksanaan kegiatan ini menggunakan metode observasi, wawancara dan dokumentasi untuk mendapatkan data dan informasi terkait dengan implementasi gerakan sekolah sehat di SDN 26 Mataram. Implementasi Gerakan Sekolah Sehat telah menunjukkan hasil yang menyenangkan dalam berbagai aspek kesehatan fisik, mental, dan kebersihan lingkungan sekolah. Meskipun masih ada beberapa tantangan dalam pelaksanaanya, partisipasi aktif dari seluruh komponen sekolah, orang tua, dan masyarakat sangat penting dalam memastikan keberhasilan gerakan ini. Gerakan Sekolah Sehat dapat terus berkembang dan memberikan manfaat jangka panjang bagi siswa, sekolah, dan masyarakat secara keseluruhan.